2015
DOI: 10.13075/ijomeh.1896.00237
|View full text |Cite
|
Sign up to set email alerts
|

Do all types of restructuring threaten employees’ well-being? An exploratory study

Abstract: Objectives: Most research on the negative impact of restructuring on employees' health considers restructuring involving personnel reduction. The aim of this study was to explore the assumption that the type of restructuring, business expansion versus restructuring not involving expansion (only reductions and/or change of ownership), influences its psychological responses: appraisal of the change, psychosocial working conditions and well-being after the change. Material and Methods: The study was carried out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 34 publications
(44 reference statements)
4
8
1
3
Order By: Relevance
“…Only one prior study examined and found a positive association between downsizing and role ambiguity [16], although the present study did not replicate this association. Of the five prior studies that explored work autonomy, there was some support in four studies for a negative association between downsizing and work autonomy [14,[16][17][18], whereas one study failed to find an association [15]. Consistent with the study by Østhus [15], the present study also failed to find a significant association between downsizing and work autonomy.…”
Section: Association Of Downsizing With Work Conditionscontrasting
confidence: 99%
See 4 more Smart Citations
“…Only one prior study examined and found a positive association between downsizing and role ambiguity [16], although the present study did not replicate this association. Of the five prior studies that explored work autonomy, there was some support in four studies for a negative association between downsizing and work autonomy [14,[16][17][18], whereas one study failed to find an association [15]. Consistent with the study by Østhus [15], the present study also failed to find a significant association between downsizing and work autonomy.…”
Section: Association Of Downsizing With Work Conditionscontrasting
confidence: 99%
“…These results support and extend past research. In terms of work role conditions, our results support prior findings that downsizing is positively associated with work demands [14][15][16]18]. The results extend prior research by showing that downsizing is positively associated with role conflict.…”
Section: Association Of Downsizing With Work Conditionssupporting
confidence: 88%
See 3 more Smart Citations